A38 Te Ara Mua Future Streets Design: Retrofitting neighbourhood routes to optimise public health. Issue 2 (June 2015) - Mackie, Hamish; Charlton, Samuel; Hosking, Jamie; Hoskins, Rau; Baas, Peter; Macmillan, Alex; Woodward, Alistair
Abstract: Background: The social and financial burden of road traffic injury in New Zealand is high compared with many other developed countries. In addition, the population is affected by chronic diseases such as obesity, diabetes and cardiovascular disease, all of which share physical inactivity as a risk factor. Road safety is currently a major objective of transport policy, while other public health outcomes are often ignored. There is a need to better understand the integrated outcomes that may arise from neighbourhood streets and routes that facilitate active travel through evidence-based design. We aimed to combine best evidence from the literature with a participatory process to design the retrofitting of urban streets. The intervention design is one part of Te Ara Mua - Future Streets, which aims to make walking and cycling safer and easier in the streets and off-road routes around Mangere Central, while reflecting the identity of Mangere people. Methods: A programme of route improvements in Mangere Central, South Auckland, is planned to improve road safety and increase active travel. The design approach combined 'Self Explaining Roads' and 'Safe System' principles with evidence from the peer-reviewed and grey literatures about effective interventions to encourage walking and cycling. A comprehensive participatory design and data collection process underpinned the intervention development. From this process, key community issues and perspectives were identified and design principles developed. Design concepts were then developed for the area and following a 'design review' process a scheme will be confirmed for detailed design. The project has also invoved a mana whenua design process, to incorporate into the design Mātauranga Māori as well as allowing mana whenua to broker wider cultural input. Results: Design features include iconic off-road shared paths, road space re-allocation for active modes, inherently safe and user-friendly crossings, highly legible accesses to key destinations and a very legible road hierarchy for motorists. Where appropriate, vehicles speeds will be managed to reflect the importance and vulnerability of active road users. The road changes are currently being programmed for construction and the evaluation is taking place before and after this. Conclusions: The project has implications for community street design practices in Auckland and New Zealand, along with the economic considerations that might lead to street and route design choices by local authorities in the future. In addition, we are demonstrating a generalizable process for successful participatory neighbourhood design.